Protection of Indigenous Peoples' Rights: A Legal Review of Local Wisdom-Based Natural Resource Management - Henny Saida Flora; Deassy J.A. Hehanussa; Fathullah Fathullah (PT. Anagata Sembagi Education, 2026)
This article examines the protection of indigenous peoples' rights in local wisdom-based natural resource management in Indonesia from the perspective of national and international law. This research is normative in nature, using legislative, conceptual, and historical approaches. The results show that although the national legal framework has recognized customary rights and local wisdom of indigenous peoples, its implementation still faces significant structural, institutional, and normative obstacles. Overlapping regulations between forestry, mining, plantation, and agrarian laws often harm the rights of indigenous peoples. On the other hand, international legal instruments such as ILO Convention No. 169 and the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) provide minimum standards of protection that have not been fully adopted by the Indonesian legal system. This article concludes that there is a need for regulatory harmonization, the establishment of specific laws for indigenous peoples, and the strengthening of indigenous institutions in natural resource management to realize ecological justice and sustainable environmental governance rooted in local wisdom values.